Quality assessment of alternative patent fingerprint method using alcohol gel and thermal paper - Chialeexian Chelladurai,; Hamzah Noor Hazfalinda,; Gabriel Gina Francesca,; Khairunnisa Zaidan,; Khairul Osman, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Fingerprints are unique structures made up of a combination of friction ridges. Due to the individual characteristics of fingerprints, it is used commonly used for identification. Traditionally, patent fingerprints are obtained using an ink pad. Unfortunately, the print takes time to dry on paper and sometimes the fingerprint will leave streaks on a finger and nearby surfaces. Alcohol gel and thermal paper could address this problem as the alcohol component in gel is a weak acid that can reacts with the leuco dyes present on thermal paper. Hence forth, this study intends to find an alternative method of obtaining patent fingerprints using various combinations of alcohol gels and thermal papers. Six donors were requested to deposit their fingerprints on different types of thermal paper using different brands of alcohol gel hand sanitisers. Quality scores based on CAST’s grading scheme were used to determine the fingerprint quality using various combinations of thermal paper and hand sanitisers. The result showed that patent fingerprints developed using hand sanitiser and thermal paper were of lower quality than the standard (ink pad). Combination of alcohol-based hand sanitiser, which consists of 70% alcohol concentration and ATM receipt paper was found to be able to produce the best quality fingerprint among the studied combinations. Despite this result, it still indicates that fingerprints using an ink pad is still the best method to record a fingerprint.